RELATIONSHIP BETWEEN MORPHOLOGICAL CHARACTERISTICS AND PHYSICAL ABILITIES IN VOLLEYBALL PLAYERS - Goran Glamočić; Branislav Strajnić; Branko Đukić; Vladimir Ivanek (Sport Scientific And Practical Aspects, 2025)
This research aims to determine the relationship between morphological characteristics and abilities in volleyball players. It was conducted on the territory of Vojvodina autonomous province on a sample of 27 male volleyball players with an average age of 17.48 ± 0.50 years and an average sports experience of 6.33 ± 2.83 years. A test battery consisting of five variables for measuring morphological characteristics and twelve tests of abilities was applied: flexibility, speed, agility, endurance, static and explosive power. The normality of the data distribution was controlled by the Shapiro-Wilk test, and the connection between morphological characteristics and abilities was calculated by the Spearman ro correlation coefficient. The limit value for testing the normality of distribution of p>0.05 was not met by: body mass index (p = 0.01), straddle in supine position (p = 0.03), single leg counter movement jump with the left leg (p = 0.01) and Yo-Yo Intermittent endurance test level 2 (p = 0.02). The connection of morphological characteristics with explosive power tests is especially noticeable, the most significant is the range of arms span with continuous jump with bent legs (ro = 0.75), single leg counter movement jump with the right leg (ro= 0.74) and Counter movement jump (ro = 0.63). The main finding in this study is that morphological characteristics are mostly negatively correlated with the explosive power of volleyball players. It is known that these characteristics and abilities have a significant share in the model of the ideal volleyball player and therefore their negative connections, the approach to the selection of volleyball and volleyball training must be based on scientific knowledge.